ANTIMICROBIAL IN VITRO SUSCEPTIBILITY OF SALMONELLA ENTERICA ISOLATED FROM GUINEA PIGS OF FAMILIAR-COMMERCIAL BREEDING SYSTEMS IN THE PROVINCE OF CARHUAZ, ANCASH - Matsuura S., Annie (2010)
The objective of the present study was to determine the sensitivity of Salmonella enterica to 12 antibiotics. The bacteria were isolated from guinea pigs showing clinical signs compatible to salmonellosis. Samples of spleen, liver and other organs showing pathological lesions were collected from unhealthy guinea pigs bred under a familiarcommercial system in the province of Carhuaz, Ancash between May to July 2007. Conventional methods were used in order to isolate S. enterica strains and the diffusion test of Kirby-Bauer method was used to evaluate the sensitivity to antibiotics. Strains of S. enterica were isolated from 61.5% of the animals. All of these strains (40/40) were sensible to enrofloxacin, sulfatrimethoprim, streptomycin, and amoxicillin, 97.5% to chloramphenicol and gentamicin, and 92.5% to fosfomicin. Resistant strains were found to furazolidone (15.0%) and colistin (12.5%) among others. The results showed that sensitivity to enrofloxacin and sulfatrimethoprim, as well as chloramphenicol, gentamicin and fosfomicin indicated these antibiotics are good choices for salmonelosis treatment in the studied farms.